Controllable thermal expansion of large magnitude in chiral negative Poisson's ratio lattices. Issue 7 (17th April 2015) - Ha, Chan Soo; Hestekin, Eric; Li, Jianheng; Plesha, Michael E.; Lakes, Roderic S.
Abstract Lattices of controlled thermal expansion are presented based on planar chiral lattice structure with Poisson's ratio approaching <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1wg4fd20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−1</alternatives>. Thermal expansion values can be arbitrarily large positive or negative. A lattice was fabricated from bimetallic strips and the properties analyzed and studied experimentally. The effective thermal expansion coefficient of the lattice is about <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1wg4fd1f" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α=−3.5×10−4</alternatives>K<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1wg4fczt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−1</alternatives>. This is much larger in magnitude than that of constituent metals. Nodes were observed to rotate as temperature was changed corresponding to a Cosserat thermoelastic solid.